UNDERSTANDING THE DETERMINANTS OF QUALITY ASSESSMENT OF IN ROAD PUBIC TRANSPORTTION-A SEVQUAL APPROACH - Sidhardha, Dr.D. (The journal of contemporary issues in business and government, 2022)
Typically service is an element that is intangible in nature and can be delivered out of an interaction between the provider of service and the customer or through the technical systems of the service provider to the customer . Because of the inherent characteristics of the service, it varies from person to person and system to system. Hence, determining quality in service is indescribable for a particular person or system. According to Philip Kotler and Gary Armstrong 'service quality' is "the ability of a service firm to hang on to its customer”